Role Play: The Relationship between Self-concept and Learner Participation in an Experiential Learning Process - Naginder Kaur A/P Surjit Singh (UUM Press, 2004)
This study was carried out to find out how far students' self-concept affect their participation in the experiential learning process of role play and the extent of improvement in their self-concept as a result of participation in the role play activities. The study was guided by the four steps in Kirk's (1987) Cycle of Experiential Learning: Do, Review, Learn, Apply. Although an individual's general self-concept is determined by the interplay of various facets, only three facets of self-concept were explored, which are, Academic Self-concept, Emotional Self-Concept andSocia1 Self- Concept. The research design adopted was that of a qualitative case study. Five participants from the Pre-Commerce course of UiTM Arau Campus were selected based on homogenous characteristics. Fourteen hours of role plays were conducted and data were gathered through classroom observations, journal entries and interviews with the students and their lecturer; who was the key informant. Several pertinent themes emerged from the data. It was found that there is a positive relationship between self-concept and students' participation in role play. This could be seen from several indicators such as prolonged nervousness, language proficiency, peer influence, the role of lecturer; the impact of dominators, task suitability as well as learners' moods. It was also found that the participants experienced a certain degree of improvement in their self-concept, as reflected by reduced anxiety, an awareness of their strengths, weaknesses and gaining of insights into the situations, improvement in language proficiency, positive relationship among peers and adaptability to the tasks. It can be concluded that role play is a profitable learning activity and is useful towards improving students' self-concept.